Hubungan Peran Guru dengan Sikap Siswa dalam Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) - Hendro Wahyudi; Niken Ayu Merna Eka Sari (Journal on Education, 2024)
School-aged children are a vulnerable period because they are in a very rapid phase of growth and development, therefore it is necessary to instill understanding and maintenance habits early, one of which is through implementing clean and healthy living behavior (PHB). The implementation of PHBS can be carried out in the school environment, this aims to create a conducive learning atmosphere. Apart from supporting facilities, the role of teachers is very necessary to accompany and motivate students in implementing PHBS. This research aims to determine the relationship between the role of teachers and students' attitudes in implementing PHBS in the school environment. This research is a descriptive correlational study with a cross sectional approach. The total population in this study was 33 people, the sampling technique was the Nonprobability Sampling technique with a total sampling of 33 respondents. The data analysis used was the spearmen rank correlation test with a significance of p <0.05. The research results show that the role of teachers towards PHBS is mostly lacking as many as 17 respondents (51.5%), students' attitudes towards PHBS are mostly sufficient as many as 17 respondents (51.5%) and based on the results of data analysis the p value is obtained. p 0.233, which means there is a relationship between the teacher's role and students' attitudes in implementing PHBS at school.